1990
DOI: 10.1029/jd095id12p20519
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric ClONO2, HCl, and HF concentration profiles derived from Atmospheric Trace Molecule Spectroscopy Experiment Spacelab 3 observations: An update

Abstract: Updated volume mixing ratio profiles of C1ONO2, HC1, and HF are reported from a reanalysis and reinterpretation of solar infrared absorption spectra obtained with the Atmospheric Trace Molecule Spectroscopy instrument on board Spacelab 3 (April 29 to May 6, 1985). These analyses incorporate improved spectroscopic parameters as well as instrumental and observational corrections made to this series of infrared spectra. While the HC1 and HF results and their precisions reflect changes essentially below 30 km from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…From the various independent results derived here, it can be concluded that the overall chlorine loading at the top of the stratosphere over the 20 to 49øN latitudinal zone was equal to 3.51 ppbv at the time of the November 1994 ATLAS-3 mission, with a 1-sigma uncertainty of 0.15 ppbv or 4%; this uncertainty represents an estimated accuracy assessed as in previous investigations [Zander et al, 1990;Gunson et al, 1990]. Throughout the stratosphere, the Clzoz VMR profiles combining the important sources, sinks and reservoirs display consistent values which suggest only second order local deficit and a mean slope reflecting the time for air to mix from the lower to the upper stratosphere.…”
Section: Table 1 Provides Numerical Values For Cl•o• and Ccly For Thsupporting
confidence: 65%
“…From the various independent results derived here, it can be concluded that the overall chlorine loading at the top of the stratosphere over the 20 to 49øN latitudinal zone was equal to 3.51 ppbv at the time of the November 1994 ATLAS-3 mission, with a 1-sigma uncertainty of 0.15 ppbv or 4%; this uncertainty represents an estimated accuracy assessed as in previous investigations [Zander et al, 1990;Gunson et al, 1990]. Throughout the stratosphere, the Clzoz VMR profiles combining the important sources, sinks and reservoirs display consistent values which suggest only second order local deficit and a mean slope reflecting the time for air to mix from the lower to the upper stratosphere.…”
Section: Table 1 Provides Numerical Values For Cl•o• and Ccly For Thsupporting
confidence: 65%
“…Although no C1ONO2 values exist for the undisturbed Arctic atmosphere our measured columns, compared to midlatitude values of 1.1x1015 mol cm -2 [Zander et al, 1990], show that the Arctic atmosphere during March is disturbed to a high extent.…”
Section: Resultsmentioning
confidence: 99%
“…CFeO abundances have also been determined from infrared spectra taken during balloon flights in October 1979 and April 1989, suggesting an increase of some 10 percent per year [Rinsland et al, 1990]. In the CFC10 measurements [Wilson et al, 1989], tropospheric mixing ratios were always found to be below the detection threshold of 4 pptv, while stratospheric mixing ratios seldom exceeded 20 pptv and here-exceeded 30 pptv.…”
Section: Concern About the Possible Implications Of Increasing Amountmentioning
confidence: 99%